2013
DOI: 10.1002/oby.20129
|View full text |Cite
|
Sign up to set email alerts
|

The association between acanthosis nigricans and dysglycemia in an ethnically diverse group of eighth grade students

Abstract: The purpose of this study was to describe the prevalence of acanthosis nigricans (AN) and to quantify its association with dysglycemia in an ethnically diverse group of eighth grade students. Data were collected in 2003 from a cross-sectional study of students from 12 middle schools in three U.S. states. Sex, race/ethnicity and pubertal status were self-reported. Anthropometric measures were recorded. Trained staff identified the presence and severity of AN by inspection of the back of the neck. Fasting and 2h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…[10] AN has been found more often among overweight or obese individuals in ethnic groups that typically experience a higher incidence of type 2 diabetes, including African Americans, Hispanics, American and Canadian Indians, Japanese, Pacific Islanders, Asian and Middle Eastern populations. [11] Data is also suggestive of significant univariate association between AN and BMI. [12] Studies have shown that about 7% of young American males have impaired glucose tolerance (IGT), with higher prevalence of impaired fasting glucose (IFG) in overweight adolescents (17.8%).…”
Section: Discussionmentioning
confidence: 87%
“…[10] AN has been found more often among overweight or obese individuals in ethnic groups that typically experience a higher incidence of type 2 diabetes, including African Americans, Hispanics, American and Canadian Indians, Japanese, Pacific Islanders, Asian and Middle Eastern populations. [11] Data is also suggestive of significant univariate association between AN and BMI. [12] Studies have shown that about 7% of young American males have impaired glucose tolerance (IGT), with higher prevalence of impaired fasting glucose (IFG) in overweight adolescents (17.8%).…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that AN imposes additional risk for dysglycemia over that from obesity alone. Hence, Rafalson et al concluded that AN is an easily identifiable clinical marker of impaired glucose tolerance and high-risk glycated hemoglobin 32. However, although most studies report that AN is a clinical indicator of underlying IR, some authors believe that AN is not an independent marker of IR 94,95…”
Section: The Impact Of An On Obese Adolescentsmentioning
confidence: 99%
“…Lesion is localized on neck, axillary and inguinal areas, especially. It is associated with insulin resistance, obesity, malignancy, and diabetes mellitus [9]. In this case, axillary acanthosis nigricans was Glucose (mg/dL) 518 0 described and hyperinsulinemia with suspect type II diabetes mellitus was identified by laboratory findings.…”
Section: Discussionmentioning
confidence: 74%